The Trips Agreement in the Legal System of World and in Legislation of Uzbekistan - Oybek Yakubov (Genius Journals, 2023)
Protecting the results of intellectual activity remains one of the most urgent problems of the modern world. Depending on the field of application, the concept of intellectual property can be interpreted differently. In a general sense, intellectual property is the right to the results of scientific, artistic, production and mental activity of a person. This article deals with the issues of documents and treaties of the WTO, in particular TRIPS. The two most important principles of the WTO legal system are the national regime and the convenience regime, which are called the principles of non-discrimination. These principles provide for the prohibition of discrimination between similar goods and services of different participating countries.
Keywords: WTO; TRIPS; Uruguay Round; National regime